The ecological function of intertidal seagrass for sediment entrapment on middle Bank Shoal, Penang / Nur Asilah Awang - Nur Asilah , Awang (2020)
Application of seagrass in eco-engineering for sustainable coastal protection requires a deeper understanding of seagrass functions for sediment entrapment. Knowledge gaps on the influence of intertidal seagrass in trapping sediments raised two main questions in this study; (1) what is the relationship between intertidal seagrass meadow structure and trapped sediment? and (2) which part of the intertidal seagrass meadow structure best explains the variability of trapped sediment? To answer these questions, seagrass shoot density, Leaf Area Index (LAI), and total aboveground biomass were used as predictors for sediments deposition rate on Middle Bank Shoal. Three seagrass species were found; Enhalus acoroides, Thalassia hemprichii, and Halophila ovalis, with shoot density, LAI, and total aboveground biomass ranged from 140-6181 shoot.m-2, 1.60-10.03 m2.m-2, 26.28-295.79 gDW.m-2, respectively, while total sediment deposition ranged from 3956 to 13237 gDW.m-2.day-1. Sediment deposition had a strong negative relationship with total aboveground biomass (R2 = 0.49, p<0.05). Low sediment deposition in high aboveground biomass suggested seagrass reduced the deposition of both primary and resuspended sediment. Being an intertidal and multispecific meadow, seagrass functions for sediment entrapment probably focused more on retaining sediments from resuspension than deposition of suspended sediments.